TiFe-based alloy with dispersed Y phase and preparation method of TiFe-based alloy
By designing TI47.5y2.5Fe40MN10 alloys and adopting the preparation method of vacuum arc melting and ultrasonic treatment, it solves the problem of difficulty in activating TIFE alloy activation and insufficient hydrogen storage performance. Suitable for large -scale applications.
Patent Information
- Application Number
- CN202411492425.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
Smart Images

Figure CN119351849A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a TiFe-based alloy with dispersed Y phase and a preparation method thereof. Background Art
[0002] Energy is the main artery of national industry and economy, and is an important consumable in human life. At present, the whole society relies on fossil energy, and fossil fuels provide more than 80% of the world's energy consumption. However, fossil energy is a non-renewable energy, and the increasing consumption of fossil energy will eventually lead to an energy crisis. In addition, the use of fossil energy also leads to environmental pollution, which will lead to greenhouse effect, haze weather and acid rain. The use of renewable clean energy can effectively solve the energy crisis and environmental pollution. Therefore, it is necessary to accelerate the transformation of energy.
[0003] At present, major economies around the world are exploring renewable clean energy that can replace fossil energy, but most clean renewable energy sources, such as wind energy and solar energy, cannot be stably supplied due to the influence of region, climate and time. Hydrogen energy has a wide range of sources, and its production is not restricted by region, climate and time. It has a high calorific value when burned, and the product is water without pollution. As an emerging energy source, hydrogen energy is considered an ideal substitute for fossil energy by developed countries such as Japan, the United States and Germany.
[0004] The large-scale use of hydrogen energy is inseparable from production, storage and transportation. At present, my country's hydrogen production enterprises have a certain scale, and the annual hydrogen production reaches more than 33 million tons. The production of hydrogen is not the main problem restricting the application of hydrogen energy in my country at this stage. How to achieve safe and efficient storage and transportation and deliver hydrogen to the application end is an urgent problem to be solved now. At present, the mainstream hydrogen storage methods are gaseous hydrogen storage, liquid hydrogen storage and solid hydrogen storage. Solid hydrogen storage is considered to be a potential storage method because of its high safety and small size.
[0005] TiFe-based hydrogen storage alloys are considered to be materials with practical application prospects because of their low price and ability to absorb and release hydrogen at near room temperature. However, this system alloy has a well-known problem, namely, difficulty in activation. At present, the mainstream improvement method is element replacement, which improves the activation performance by adding different elements to the alloy. This method has a disadvantage. Although the activation performance of the alloy may be improved after adding other elements, the addition of other elements will inevitably affect other performance aspects, such as causing a decrease in hydrogen storage capacity, a slowdown in hydrogen absorption rate, and a decrease in cycle stability. In addition, some added elements are costly or chemically active, such as Sc, La, etc., which are difficult to smelt and prepare and actually use, affecting production safety, and will also lead to an increase in the pressure required for hydrogen absorption, which will reduce the safety of use and greatly increase the cost of hydrogen absorption alloy devices, limiting large-scale applications. The co-addition of multiple elements has been widely explored in scientific research, but it will lead to severe component segregation in large-scale traditional smelting, and the difficulty of preparation hinders its large-scale application. Therefore, it is of great significance to design simple, safe, and low-cost alloy composition and further explore new process methods to improve the hydrogen storage performance of TiFe-based alloys for promoting the widespread application of hydrogen energy. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of difficulty in activating the existing TiFe alloy, high activation temperature and hydrogen absorption pressure, difficulty in achieving good activation, hydrogen absorption rate and cycle life, high alloy cost and unsuitability for large-scale preparation, and propose a TiFe-based alloy with a dispersed Y phase and a preparation method thereof.
[0007] The present invention discloses a TiFe-based alloy with dispersed Y phase, which is composed of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn in atomic percentage, and has a chemical formula of Ti 47.5 Y 2.5 Fe 40 Mn 10 .
[0008] The preparation method of a TiFe-based alloy having a dispersed Y phase of the present invention is carried out by the following steps:
[0009] 1. According to the atomic percentage of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn, Ti, Y, Fe and Mn metal single substance particles are weighed to obtain raw materials;
[0010] 2. Place the raw materials in the crucible of the melting furnace, evacuate the furnace, introduce argon gas, and then perform vacuum arc melting. After repeated melting, an ingot is obtained.
[0011] 3. After the ingot is melted, ultrasonic waves are applied, and then the arc melting power is turned off to solidify under ultrasonic conditions to obtain Ti with high hydrogen storage performance.47.5 Y 2.5 Fe 40 Mn 10 alloy.
[0012] The present invention has the following beneficial effects:
[0013] 1. The present invention adjusts the composition and content of the alloy, adds 2.5 at.% of Y element, and provides a TiFe-based hydrogen storage alloy with the general formula of Ti 47.5 Y 2.5 Fe 40 Mn 10 , introducing dispersed fine Y phase, greatly shortening the activation incubation period of the alloy under lower pressure. The overall composition is simple, the price is low, and the hydrogen storage performance of the alloy is effectively improved. At 100℃ and 3.5MPa hydrogen pressure, the incubation time is greatly shortened, and activation can be achieved by absorbing and releasing hydrogen once. In the room temperature range, the alloy has excellent hydrogen storage capacity and fast hydrogen absorption rate at only 3.5MPa hydrogen pressure. The hydrogen storage capacity at 30℃ can reach 1.73wt.%, and the hydrogen absorption within 120s can reach more than 90% of the maximum hydrogen storage capacity.
[0014] 2. The present invention introduces ultrasonic treatment during the alloy smelting process to regulate the alloy's organizational morphology without changing the alloy's phase composition. While maintaining a rapid hydrogen absorption rate, the alloy's activation performance and hydrogen storage capacity are further improved, and the alloy has a good cycle life, maintaining more than 90% of its hydrogen storage capacity after 200 cycles.
[0015] 3. The present invention adds a trace amount of Y element and introduces a dispersed fine Y phase, which significantly improves the activation and hydrogen storage rate of the alloy. By introducing ultrasonic treatment during the smelting process, the two work together to comprehensively improve the hydrogen storage capacity and cycle life of the hydrogen storage alloy. The alloy composition and process are simple, the preparation is convenient and the cycle is short, and it is easy to implement. It is a promising method for improving the hydrogen storage performance of the alloy, which is conducive to large-scale preparation and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Ti prepared in Examples 1, 2 and 3 of the present invention 50 Fe 40 Mn 10 Ti 47.5 Y 2.5 Fe 40 Mn 10 X-ray diffraction pattern of the alloy;
[0017] Figure 2 The Ti prepared in Example 1 of the present invention 50 Fe 40 Mn 10 SEM microstructure of the alloy;
[0018] Figure 3 The Ti prepared in Example 2 of the present invention 47.5 Y 2.5 Fe 40 Mn 10 SEM microstructure of the alloy;
[0019] Figure 4 The Ti prepared in Example 3 of the present invention 47.5 Y 2.5 Fe 40 Mn 10 SEM microstructure of the alloy;
[0020] Figure 5 is the Ti prepared in Example 1 50 Fe 40 Mn 10 Activation hydrogen absorption curve of the alloy at 100℃ and 3.5MPa hydrogen;
[0021] Figure 6 is the Ti prepared in Example 2 47.5 Y 2.5 Fe 40 Mn 10 Activation hydrogen absorption curve of the alloy at 100℃ and 3.5MPa hydrogen;
[0022] Figure 7 is the Ti prepared in Example 3 47.5 Y 2.5 Fe 40 Mn 10 Activation hydrogen absorption curve of the alloy at 100℃ and 3.5MPa hydrogen;
[0023] Figure 8 is the Ti prepared in Example 2 47.5 Y 2.5 Fe 40 Mn 10 Hydrogen absorption kinetic curves of the alloy at 20℃ and 30℃, 3.5MPa hydrogen;
[0024] Fig. 9 is the Ti prepared in Example 3 47.5 Y 2.5 Fe 40 Mn 10 Hydrogen absorption kinetic curves of the alloy at 20℃ and 30℃, 3.5MPa hydrogen;
[0025] Fig.10 is the Ti prepared in Example 3 47.5 Y 2.5 Fe 40 Mn 10The relationship between the hydrogen storage capacity and the number of cycles of the alloy at 30°C and 3.5MPa hydrogen. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0027] Specific implementation method 1: In this implementation method, a TiFe-based alloy with a dispersed Y phase is composed of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn in atomic percentage, and the chemical formula is Ti 47.5 Y 2.5 Fe 40 Mn 10 .
[0028] Specific implementation method 2: In this implementation method, a preparation method of a TiFe-based alloy having a dispersed Y phase is carried out according to the following steps:
[0029] 1. According to the atomic percentage of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn, Ti, Y, Fe and Mn metal single substance particles are weighed to obtain raw materials;
[0030] 2. Place the raw materials in the crucible of the melting furnace, evacuate the furnace, introduce argon gas, and then perform vacuum arc melting. After repeated melting, an ingot is obtained.
[0031] 3. After the ingot is melted, ultrasonic waves are applied, and then the arc melting power is turned off to solidify under ultrasonic conditions to obtain Ti with high hydrogen storage performance. 47.5 Y 2.5 Fe 40 Mn 10 alloy.
[0032] Specific implementation method 3: This implementation method is different from the specific implementation method 2 in that the purity of the Mn particles is greater than 99.7%, and the purity of Ti, Y and Fe is greater than 99.9%. Other aspects are the same as the specific implementation method 2.
[0033] Specific embodiment 4: This embodiment differs from specific embodiment 2 or 3 in that: Step 2: vacuumize to 3×10 -3 Pa, and then argon is introduced to 0.05MPa. Other aspects are the same as those of the second or third embodiment.
[0034] Specific implementation method 5: This implementation method is different from specific implementation methods 2 to 4 in that the vacuum melting current is 350 to 450 A and the melting time is 25 to 35 seconds. The rest is the same as specific implementation methods 2 to 4.
[0035] Specific implementation method 6: This implementation method is different from specific implementation methods 2 to 5 in that the melting is repeated 3 to 5 times in step 2. The rest is the same as specific implementation methods 2 to 5.
[0036] Specific embodiment 7: This embodiment differs from specific embodiments 2 to 6 in that the ultrasonic power in step 3 is 20.5 kHz and the output amplitude is 20 μm. The rest is the same as specific embodiments 2 to 6.
[0037] Specific embodiment 8: This embodiment is the same as any one of specific embodiments 2 to 7 in that: in step 3, after applying ultrasound for 80 to 120 seconds, the arc melting power source is turned off. Other aspects are the same as any one of specific embodiments 2 to 7.
[0038] The following examples are used to verify the beneficial effects of the present invention:
[0039] Embodiment 1: This embodiment provides a TiFe-based alloy and a preparation method thereof. The composition of the TiFe-based hydrogen storage alloy is as follows: 50 Fe 40 Mn 10 , and its preparation method is as follows:
[0040] (1) According to the atomic ratio of the above components, Ti, Fe and Mn metal particles are weighed, the purity of the Mn particles is greater than 99.7%, and the purity of the remaining materials is greater than 99.9%, to obtain raw materials before alloy smelting.
[0041] (2) Place the raw materials in the same crucible of the melting furnace and evacuate to 3×10 -3 After the temperature reaches 0.05 MPa, the protective gas argon with a purity higher than 99.9% is introduced, and then vacuum arc melting is performed. The melting is repeated 4 times to ensure uniform composition and obtain Ti 50 Fe 40 Mn 10 Alloy ingot. The vacuum melting current is 400A and the melting time is 30s.
[0042] Experimental test:
[0043] (1) Use wire cutting machine to cut Ti 50 Fe 40 Mn 10 A 10 mm × 10 mm × 9 mm piece was cut from the center of the alloy ingot, and the surface was ground and polished to a mirror finish, and then X-ray diffraction detection and scanning electron microscope observation were performed.
[0044] (2) Ti will be obtained 50 Fe 40 Mn 10The alloy ingot was polished with 200-grit sandpaper to remove surface stains and oxide scale. The polished alloy ingot was placed in an ultrasonic cleaning machine, the cleaning agent was anhydrous ethanol, the ultrasonic frequency was 30kHz, the cleaning time was 10 minutes, and the alloy ingot was blown dry after cleaning.
[0045] (3) Mechanically crushing the polished and cleaned alloy ingot, screening and crushing to particles between 100 mesh and 200 mesh, and obtaining Ti 50 Fe 40 Mn 10 Alloy particles.
[0046] (4) Take 2 g of alloy particles and put them into a reactor, and activate them at 100°C and 3.5 MPa H2.
[0047] Result analysis:
[0048] Ti prepared in Example 1 50 Fe 40 Mn 10 The alloy is mainly composed of TiFe phase and TiMn2 phase. Figure 1 The scanning electron microscope microstructure of the alloy is shown in Figure 2 As shown in the figure, the structure is fine and uniform, without coarse dendrites. The alloy begins to absorb hydrogen after a 4360-second incubation period at 100°C and 3.5MPa H2. The sample can be fully activated after 220 minutes of hydrogen absorption. Figure 5 shown.
[0049] Example 2
[0050] This embodiment provides a TiFe-based alloy and a preparation method thereof. The composition of the TiFe-based hydrogen storage alloy is as follows: Ti 47.5 Y 2.5 Fe 40 Mn 10 , and its preparation method is as follows:
[0051] (1) According to the atomic ratio of the above components, Ti, Y, Fe and Mn metal particles are weighed, the purity of the Mn particles is greater than 99.7%, and the purity of the remaining materials is greater than 99.9%, to obtain raw materials before alloy smelting.
[0052] (2) Place the raw materials in the same crucible of the melting furnace and evacuate to 3×10 -3 After the temperature reaches 0.05 MPa, the protective gas argon with a purity higher than 99.9% is introduced, and then vacuum arc melting is performed. The melting is repeated 5 times to ensure uniform composition and obtain Ti 47.5 Y 2.5 Fe 40 Mn 10Alloy ingot. The vacuum melting current is 400A and the melting time is 30s.
[0053] Experimental test:
[0054] (1) Use wire cutting machine to cut Ti 50 Fe 40 Mn 10 A 10 mm × 10 mm × 9 mm piece was cut from the center of the alloy ingot, and the surface was ground and polished to a mirror finish, and then X-ray diffraction detection and scanning electron microscope observation were performed.
[0055] (2) The ultrasonically treated Ti 47.5 Y 2.5 Fe 40 Mn 10 The alloy ingot was polished with 200-grit sandpaper to remove surface stains and oxide scale. The polished alloy ingot was placed in an ultrasonic cleaning machine, the cleaning agent was anhydrous ethanol, the ultrasonic frequency was 30kHz, the cleaning time was 10 minutes, and the alloy ingot was blown dry after cleaning.
[0056] (3) Mechanically crushing the polished and cleaned alloy ingot, screening and crushing to particles between 100 mesh and 200 mesh, and obtaining Ti 47.5 Y 2.5 Fe 40 Mn 10 Alloy particles.
[0057] (4) 2 g of alloy particles were placed in a reactor and activated at 100 °C and 3.5 MPa H2, followed by a hydrogen absorption kinetic test at 20 °C and 30 °C and 3.5 MPa.
[0058] Result analysis:
[0059] Example 2 Preparation of Ti 47.5 Y 2.5 Fe 40 Mn 10 The alloy is mainly composed of TiFe phase, TiMn2 phase and Y phase. Figure 3 The scanning electron microscope microstructure of the alloy is shown in Figure 3 As shown in the figure, there are coarse dendrite TiMn2 phase and uniformly distributed fine Y phase in the structure. The alloy begins to absorb hydrogen after an incubation period of 1100 seconds at 100℃ and 3.5MPa H2. After 100 minutes of hydrogen absorption, the sample can be fully activated, as shown in the figure. Figure 6 As shown. The alloy has a hydrogen storage capacity of 1.60wt.% at 20°C and 3.5MPa H2 for 900 seconds, and a hydrogen storage capacity of 1.69wt.% at 30°C and 3.5MPa H2 for 900 seconds. Figure 8 shown.
[0060] Example 3
[0061] This embodiment provides a method for preparing a TiFe-based alloy having a dispersed Y phase, wherein the composition of the TiFe-based hydrogen storage alloy is as follows: 47.5 Y 2.5 Fe 40 Mn 10 , and its preparation method is as follows:
[0062] (1) According to the atomic ratio of the above components, Ti, Y, Fe and Mn metal particles are weighed, the purity of the Mn particles is greater than 99.7%, and the purity of the remaining materials is greater than 99.9%, to obtain raw materials before alloy smelting.
[0063] (2) Place the raw materials in the same crucible of the melting furnace and evacuate to 3×10 -3 After the vacuum arc melting, the vacuum arc melting current was 400A and the melting time was 30s.
[0064] (3) In the fifth melting, after the ingot is completely melted, the ultrasonic generator is turned on, the ultrasonic power is 20.5kHz, the output amplitude is 20μm, and the ultrasonic time is 100s. Then, the arc melting power is turned off, and the alloy melt solidifies under the action of ultrasound to obtain ultrasonically treated Ti 47.5 Y 2.5 Fe 40 Mn 10 Alloy ingot.
[0065] Experimental test:
[0066] (1) Use wire cutting machine to cut Ti 50 Fe 40 Mn 10 A 10 mm × 10 mm × 9 mm piece was cut from the center of the alloy ingot, and the surface was ground and polished to a mirror finish, and then X-ray diffraction detection and scanning electron microscope observation were performed.
[0067] (2) The ultrasonically treated Ti 47.5 Y 2.5 Fe 40 Mn 10 The alloy ingot was polished with 200-grit sandpaper to remove surface stains and oxide scale. The polished alloy ingot was placed in an ultrasonic cleaning machine, the cleaning agent was anhydrous ethanol, the ultrasonic frequency was 30kHz, the cleaning time was 10 minutes, and the alloy ingot was blown dry after cleaning.
[0068] (3) Mechanically crushing the polished and cleaned alloy ingot, screening and crushing to particles between 100 mesh and 200 mesh, and obtaining Ti47.5 Y 2.5 Fe 40 Mn 10 Alloy particles.
[0069] (4) Take 2 g of alloy particles and put them into the reactor, activate them at 100°C and 3.5 MPaH2, then carry out hydrogen absorption kinetics test at 20°C and 30°C and 3.5 MPa, and carry out 200 hydrogen absorption tests at 30°C and 3.5 MPa.
[0070] Result analysis:
[0071] Example 3 Ultrasonic treatment of Ti 47.5 Y 2.5 Fe 40 Mn 10 The alloy is mainly composed of TiFe phase, TiMn2 phase and Y phase. Figure 1 The scanning electron microscope microstructure of the alloy is shown in Figure 4 As shown in the figure, the structure is fine and uniform, without coarse dendrites, and the fine Y phase is evenly distributed. The alloy begins to absorb hydrogen after a 220-second incubation period at 100°C and 3.5MPa H2. The sample can be fully activated after 80 minutes of hydrogen absorption. Figure 7 As shown. At 20°C and 3.5MPa H2, the alloy has a hydrogen storage capacity of 1.66wt.% in 900 seconds, and at 30°C and 3.5MPaH2, the hydrogen storage capacity of 1.73wt.% in 900 seconds. The amount of hydrogen absorbed within 120s can reach more than 90% of the maximum hydrogen storage capacity, as shown Fig. 9 As shown. Ultrasonic treated Ti 47.5 Y 2.5 Fe 40 Mn 10 The alloy has been subjected to 200 hydrogen absorption cycles at 30°C and 3.5MPa, and the hydrogen storage capacity remains above 90% ( Fig.10 ).
[0072] In summary, the above embodiment provides a TiFe-based hydrogen storage alloy with uniformly distributed fine Y phase and uniform structure and a preparation method thereof. The general composition formula of the alloy is Ti 47.5 Y 2.5 Fe 40 Mn 10, the preparation method introduces ultrasonic treatment in the traditional arc melting process. The advantage of the above embodiment of the present invention is that by adding a small amount of Y, introducing a uniformly dispersed, fine Y phase, introducing ultrasonic treatment, and refining the coarse TiMn2 phase, the difficulty in activating the TiFe alloy is solved, and a TiFe-based hydrogen storage alloy with excellent comprehensive performance is obtained. The alloy has excellent comprehensive hydrogen storage performance and is easy to activate. Under the neutral temperature and pressure (100°C, 3.5MPa), it begins to absorb hydrogen after 220 seconds of incubation; it has a fast hydrogen absorption ability. At 30°C, under only 3.5MPa hydrogen pressure, the hydrogen storage capacity is 1.73wt.% within 900 seconds; it has a good cycle life. After 200 cycles, the hydrogen storage capacity remains above 90%. The alloy has a low applicable pressure, which is beneficial to the reduction of the compressive resistance index of the hydrogen storage device, and is beneficial to improving safety and reducing costs. The alloy preparation method is simple, safe, efficient, low-cost, and suitable for large-scale applications.
Claims
1. A TiFe-based alloy having a dispersed Y phase, characterized in that: The TiFe-based alloy is composed of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn in atomic percentage, and has a chemical formula of Ti 47.5 Y 2.5 Fe 40 Mn 10 .
2. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 1, characterized in that: The preparation method is carried out according to the following steps:
1. According to the atomic percentage of 47.5% Ti, 2.5% Y, 40% Fe and 10% Mn, Ti, Y, Fe and Mn metal single substance particles are weighed to obtain raw materials; 2. Place the raw materials in the crucible of the melting furnace, evacuate the furnace, introduce argon gas, and then perform vacuum arc melting. After repeated melting, an ingot is obtained.
3. After the ingot is melted, ultrasonic waves are applied, and then the arc melting power is turned off to solidify under ultrasonic conditions to obtain Ti with high hydrogen storage performance. 47.5 Y 2.5 Fe 40 Mn 10 alloy.
3. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that: The purity of the Mn particles is greater than 99.7%, and the purity of Ti, Y and Fe are all greater than 99.9%.
4. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that: Step 2: Vacuum to 3×10 -3 Pa, and then argon was introduced to 0.05MPa.
5. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that: The vacuum melting current is 350-450A, and the melting time is 25-35s.
6. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that In step 2, the smelting is repeated 3 to 5 times.
7. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that In step 3, the ultrasonic power is 20.5 kHz and the output amplitude is 20 μm.
8. The method for preparing a TiFe-based alloy having a dispersed γ phase according to claim 2, characterized in that: Features In step 3, after applying ultrasound for 80 to 120 seconds, the arc melting power source is turned off.